Individual responsibility towards providing water and wastewater public goods for displaced persons: How much and how long is the public willing to pay?. (May 2021) - Faust, K.M.; Roy, A.; Feinstein, S.; Poleacovschi, C.; Kaminsky, J.
Highlights: There is a perceived individual financial responsibility to support those displaced. Collective and individual responsibility misaligned when providing public goods. Individual responsibility is less than collective expectation of providing service. Males, and wealthier, more educated, and urban individuals are more willing to pay. This can inform utilities on rate increases to fund a portion of services. Abstract: In 2019, the number of displaced persons worldwide reached a historic peak. When those displaced arrive in hosting cities, local utilities, often with no additional money, are tasked with meeting unexpected demands. One way to recoup these costs is to raise rates. However, publics are not always willing to share their own financial resources and utilities. In this empirical study, we quantitatively assess the residents' perceived individual responsibility—or willingness to pay—for these expanded services. Here we seek to not only identify if an individual is willing to financially support the provision of services for those displaced via an increase in their own rates, but also, to quantify how long they are willing to support these services. Further, we explore factors that influence this perceived individual responsibility. Enabling this study is survey data from the German public in 2016, a time when the asylum seekers, who were displaced by instability in the Middle East, encountered increased public opposition. We find respondents who are male, wealthier, more highly educated, and more urban are more willing to pay for services for displaced populations. These results can inform awareness campaigns or changes in rates and rate structures.